The Representation of Childhood in Roald Dahl’s The Big Friendly Giant - Daempal, Anggun Ester; Mamentu, Agustin C.; Sabudu, Delli (Program Studi Pendidikan Bahasa Inggris, 2024)
This study explores the representation of childhood in Roald Dahl's